China as a new leader in the supply of medical equipment to Russia ("Journal "U". Economy. Management. Finance.", 2025)
This article is devoted to the analysis of the growth of medical equipment supplies from China to Russia. The article also examines the foreign policy and foreign economic factors that stimulate this trend. The reasons for the increase in imports of medical products are described, and the main positions that occupy a large part in the export of this industry are considered. It is important to touch upon the current trends in this topic, as well as to study the growth that has arisen from the point of view of statistics The difficulties faced by companies engaged in importing from China are considered. In conclusion, this topic discusses the prospects for the development of medical equipment imports from China to Russia.
Keywords: medical equipment; import; growth; China; economy; logistics; foreign policy factors